Legal Certainty Due To The Negligence Of The Public Prosecutor In Determining The Charges - Elizabeth, Vivi; Adhari, Ade (Syiar Hukum, 2023)
Legal certainty has an important role in upholding the law properly in accordance with the provisions used in the indictment. Seeing the important role of legal certainty, law enforcers should be careful in enforcing the law. However, this did not occur in the Decision of the Ngabang District Court Number 48/Pid.Sus/2019/PN.Nba, where the Public Prosecutor failed to determine the charges according to the actions of the defendant. The purpose this research analyasis legal certainty negligene public prosecutor choice indictment  . In this study, primary and secondary legal materials were used and analyzed using qualitative techniques. The prosecutor's negligence in determining the charges in the indictment caused legal uncertainty which resulted in the law not being enforced consistently and with certainty. The prosecutor should be more careful in determining the indictment in his decision because legal uncertainty will cause chaos and the law will not benefit the community.